Pluralité des valeurs attribuées à la nature : le rôle des instances de socialisation primaire - Véronique Van Tilbeurgh; Anne Atlan (VertigO, 2022)
While a great diversity of values is attributed to nature, the usual social determinants, such as socioprofessional category, age or gender, have proven to be of little explanatory value. This article explores the role of socialization, and more specifically of primary socialization, in the type of value that individuals assign to nature. The investigation took place in the sub-Antarctic islands: there, nature is valued in a non-utilitarian and non-market context, which allows for the expression of a wide range of values. We have analyzed the correspondence between the forms of socialization of individuals to nature and the values they assign to it. The main distinction puts into tension two instances of primary socialization: families and peer groups. Families lead to a dominant and abstract evaluation of nature whereas peer groups lead to an egalitarian and concrete evaluation. On the other hand, those who were not socialized to nature in childhood tend to emphasize the the self-esteem provided by their adult experience of nature. Although the majority of trajectories are linear, reinforcements or alterations are possible, showing that certain forms of secondary socialisation can change the values attributed to nature.